Preliminary Study on Status and Ecology of Pteropus giganteus in Aligarh City, Uttar Pradesh - Raza, Mushahid; Ilyas, Orus (Indian Forester, 2018)
Megachiropteran species Pteropus giganteus, commonly known as Indian flying fox, belongs to the Pteropodidae family. It is known as ecologically important species, with economic benefits. This species is well known for its seed dispersal and pollinating activities. Considering the importance of P. giganteus, the present study was conducted for three months (February – April, 2016), at Nagar Nigam roosting site in Aligarh district of Uttar Pradesh. To explicate the population status, bats were recorded twice in a week in the evenings before the sunset and in the early morning hours, after sunrise, by using the 'Direct roost count' method. The mean population of P. giganteus was calculated 276 in February, while in April, it was 404. Showing an increase of 46.4%, the population of P. giganteus was also facing some threats, such as electrocution and deforestation. For the variation in roosting site selection, data were collected during winter and summer seasons. During the study, the population of P. giganteus showed remarkable changes in their roost site selection. The feeding ecology of this species was examined by direct observation. A total of eight fruit plant species were identified, eaten by P. giganteus. In identified fruits that dominantly eaten by P. giganteus were Fig.